Antibacterial activity of black cumin, clove, and ginger essential oils against specific spoilage organisms of ready-to-eat chilli shrimp paste - Chan, M. T.; Mahmud @ Ab Rashid, Nor Khaizura; Mahyudin, Nor Ainy; Jamaludin, Nazzatush Shimar; Mohd Khairul, Nurul Shafiqa Atikah; Yahya, Ummul Izzatul Izzah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2021)
Ready-to-eat (RTE) chilli shrimp paste has a short shelf life; thus, chemical additives are usually added to extend it. However, certain additives have potential health implications. In this regard, plant essential oils (EOs) which exhibit antibacterial properties can be used as an alternative for extending the shelf life of RTE chilli shrimp paste. The present work intended to (1) establish the microbial profile of RTE chilli shrimp paste, (2) determine the antibacterial activities of black cumin, clove, and ginger EOs against the isolated specific spoilage organisms (SSO) of RTE chilli shrimp paste, and (3) determine their effect on the shelf life of RTE chilli shrimp paste. Biochemical tests and 16S rRNA gene sequencing were used to identify the SSO in RTE chilli shrimp paste. Disc diffusion assay was performed for antibacterial analysis of EOs. To monitor the shelf life of the paste, total plate count (TPC) and yeast and mould count (YMC) were carried out for five days. The results showed that the SSO of RTE chilli shrimp paste were dominated by Staphylococcus spp. followed by Klebsiella aerogenes and Enterobacter tabaci. EOs of black cumin, clove, and ginger showed inhibitory effects against the SSO with the highest inhibition by ginger EO of 27.50 ± 9.19 to 58.00 ± 7.21 mm. Application of ginger EO in RTE chilli shrimp paste showed a 3-log reduction of bacterial population and 4-log reduction for fungal population. It was concluded that ginger EO can be a highly potential candidate to be added into RTE chilli shrimp paste as a natural additive to extend its shelf life.